2011
DOI: 10.3741/jkwra.2011.44.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Development of Continuous Rainfall-Runoff Model for Flood Forecasting on the Large-Scale Basin

Abstract: The objective of this study is to develop a continuous rainfall-runoff model for flood prediction on a large-scale basin. For this study, the hourly surface runoff estimation method based on the variable retention parameter and runoff curve number is developed. This model is composed that the soil moisture to continuous rainfall can be simulated with applying the hydrologic components to the continuous equation for soil moisture. The runoff can be simulated by linking the hydrologic components with the storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The SURR model was developed by the Water Resource and GIS Laboratory, Sejong University [42] and is based on the event-oriented storage function model (SFM) by [43]. The SURR considers the rainfall loss using a soil moisture accounting model for streamflow simulation and prediction.…”
Section: Sejong University Rainfall-runoff (Surr) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The SURR model was developed by the Water Resource and GIS Laboratory, Sejong University [42] and is based on the event-oriented storage function model (SFM) by [43]. The SURR considers the rainfall loss using a soil moisture accounting model for streamflow simulation and prediction.…”
Section: Sejong University Rainfall-runoff (Surr) Modelmentioning
confidence: 99%
“…The rainfall and evapotranspiration data have hourly temporal resolutions, which were spatially interpolated by the Thiessen polygons method using GIS. A detailed description of the SURR model is reported in [42]. The hydrologic models simulate the response of the basin to a given rainfall.…”
Section: Sejong University Rainfall-runoff (Surr) Modelmentioning
confidence: 99%
“…Q sur (t), Q lat (t) and Q gw (t) denote the runoff components of surface flow (mm), lateral flow (mm) and groundwater flow (mm), respectively. Additional detailed mathematical descriptions of the components were provided by Bae and Lee (2011). Bae and Lee (2011) showed that the SURR simulations are well fitted to observations, and Nash and Sutcliffe model efficiencies in the calibration and verification periods which are in the ranges of 0.81 to 0.95 and 0.70 to 0.94, respectively.…”
Section: Flash Flood Guidancementioning
confidence: 99%
“…Additional detailed mathematical descriptions of the components were provided by Bae and Lee (2011). Bae and Lee (2011) showed that the SURR simulations are well fitted to observations, and Nash and Sutcliffe model efficiencies in the calibration and verification periods which are in the ranges of 0.81 to 0.95 and 0.70 to 0.94, respectively. Additionally, the behavior of soil moisture depending on the rainfall and the annual loadings of simulated hydrologic components is rational.…”
Section: Flash Flood Guidancementioning
confidence: 99%
See 1 more Smart Citation